Synthesis And Characterisation Of PEG-PLGA Nanoparticles For Geraniin Isolated From Phyllanthus watsonii (Dukung Anak) Extract - Jairaman, Sreegayathri (2018)
A growing number of drug delivery nowadays utilises nanomedicine technology. The efficiency of drug delivery to the target site in the body depends on the physico-chemical factors of the drug carrier. Phyllanthus watsonii, which is locally known as dukung anak, is found in tropical forests in Malaysia. Extracts from the plants have anti-hypertensive, anti-viral and anti-diabetes properties. Geraniin, as the major active compound from P.watsonii extract was utilized in the study which is given by Dr. Indu S Jaganath from Malaysia Agricultural Research and Development Institute (MARDI).